Hepatitis C virus RNA levels at week-2 of telaprevir/boceprevir administration are predictive of virological outcome. Issue 2 (February 2015) - Cento, Valeria; Di Paolo, Daniele; Di Carlo, Domenico; Micheli, Valeria; Tontodonati, Monica; De Leonardis, Francesco; Aragri, Marianna; Antonucci, Francesco Paolo; Di Maio, Velia Chiara; Mancon, Alessandro; Lenci, Ilaria; Manunta, Alessandra; et al.
Abstract: Background: Triple therapy with telaprevir/boceprevir + pegylated-interferon + ribavirin can achieve excellent antiviral efficacy, but it can be burdened with resistance development at failure. Aims: To evaluate kinetics of hepatitis C virus (HCV) RNA decay and early resistance development, in order to promptly identify patients at highest risk of failure to first generation protease inhibitors. Methods: HCV-RNA was prospectively quantified in 158 patients receiving pegylated-interferon + ribavirin + telaprevir ( N = 114) or + boceprevir ( N = 44), at early time-points and during per protocol follow-up. Drug resistance was contextually evaluated by population sequencing. Results: HCV-RNA at week-2 was significantly higher in patients experiencing virological failure to triple-therapy than in patients with sustained viral response (2.3 [1.9–2.8] versus 1.2 [0.3–1.7] log IU/mL, p < 0.001). A 100 IU/mL cut-off value for week-2 HCV-RNA had the highest sensitivity (86%) in predicting virological success. Indeed, 23/23 (100%) patients with undetectable HCV-RNA reached success, versus 26/34 (76.5%) patients with HCV-RNA < 100 IU/mL, and only 11/31 (35.5%) with HCV-RNA > 100 IU/mL ( p < 0.001). Furthermore, differently from failing patients, none of the patient with undetectable HCV-RNA at week-2 had baseline/early resistance. Conclusions: With triple therapy based on first generation protease inhibitors, suboptimal HCV-RNA decay at week-2 combined with early detection of resistance can help identifying patients with higher risk of virological failure, thus requiring a closer monitoring during therapy.